Evidence for production of single top quarks - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Dong, H.; et al. (Amer Physical Soc, 2008)
We present first evidence for the production of single top quarks in the D0 detector at the Fermilab Tevatron p (p) over bar collider. The standard model predicts that the electroweak interaction can produce a top quark together with an antibottom quark or light quark, without the antiparticle top-quark partner that is always produced from strong-coupling processes. Top quarks were first observed in pair production in 1995, and since then, single top-quark production has been searched for in ever larger data sets. In this analysis, we select events from a 0.9 fb(-1) data set that have an electron or muon and missing transverse energy from the decay of a W boson from the top-quark decay, and two, three, or four jets, with one or two of the jets identified as originating from a b hadron decay. The selected events are mostly backgrounds such as W + jets and t (t) over bar events, which we separate from the expected signals using three multivariate analysis techniques: boosted decision trees, Bayesian neural networks, and matrix-element calculations. A binned likelihood fit of the signal cross section plus background to the data from the combination of the results from the three analysis methods gives a cross section for single top-quark production of sigma(p (p) over bar -> tb + X, tqb + X) = 4.7 +/- 1.3 pb. The probability to measure a cross section at this value or higher in the absence of signal is 0.014%, corresponding to a 3.6 standard deviation significance. The measured cross section value is compatible at the 10% level with the standard model prediction for electroweak top-quark production. We use the cross section measurement to directly determine the Cabibbo-Kobayashi-Maskawa quark mixing matrix element that describes the Wtb coupling and find vertical bar V(tb)f(1)(L)vertical bar = 1.31(-0.21)(+0.25), where f(1)(L) is a generic vector coupling. This model-independent measurement translates into 0.68 <vertical bar V-tb vertical bar <= 1 at the 95% C.L. in the standard model.